Mediostigmaeus gen. n. (Acari: Stigmaeidae), with the description of a new species from the USA - Fan, Qing-Hai; Walter, David E. (Zootaxa, 2005)
A new genus, Mediostigmaeus is proposed for two species, M. citri (Rakha & McCoy, 1984) comb. n. and M. floridanus sp. n. The new genus is similar to Mediolata in having only one pair of subcapitular setae but can be easily distinguished by having the palptibial claw subequal to the palptarsus, and setae c 1 , d 1 , d 2 , e 1 , e 2 , and f 1 situated on individual platelets. The adult female of M. floridanus sp. n., collected from domatia of Vitis sp., Lake Adair, Orlando, Florida, USA can be separated from those of M. citri by chaetotaxy of tarsi and pattern of hysterosomal shield.